Gold Phytomining: A New Idea for Enviromental Sustainablity in Indonesia - Krisnayanti, Baiq Dewi; Anderson, Christopher (Indonesian Journal on Geoscience, 2014)
DOI: 10.17014/ijog.v1i1.171New technology is needed to protect the safety and health of communities and the environment at ASGM locations in Indonesia. This technology must be simple, cheap, easy to operate, and financially rewarding. A proven option that should be promoted is phytoextraction, a farming activity that could develop agriculture as an alternative livelihood in ASGM areas. This is a technology where plants are used to extract metals from waste rock, soil, or water. These metals can be recovered from the plant in its pure form, then be sold or recycled. Gold phytoextraction is a commercially available technology, while an international research has shown that phytoextraction will also work for mercury. In the context of this idea, tailings would be contained in ‘farming areas’ and cropped using phytoextraction technology. Gold and mercury would be extracted in the crops, with the remaining mercury burden of the tailings becoming adsorbed to soil constituents. The system would be financially rewarding to ‘gold farmers’. The economic value of this scenario could facilitate the clean-up and management of mercury pollution, reducing the movement of mercury from tailings into soil, water, and plants, thereby mitigating environmental and human risk in the mining areas. The goal of the described research is to promote agriculture as an alternative livelihood in ASGM areas. The gold value of the phytoremediation crop should provide a cash incentive to artisanal farmers who develop this new agricultural enterprise. The benefits will be social, environmental, and economic, as opportunities for education, employment, new business, the containment of toxic mercury, food safety and security, and revenue are all realized.